The Effect of Production, Price, Exchange Rate, And Trade Policy on Indonesian Tuna Exports to Japan from 2009 to 2023 - Nisa Hafi Idhoh Fitriana; Intan Savitri Ciptaningtyas (Universitas Islam Lamongan, 2025)
Tuna is an essential commodity in the fishing and marine due to its high economic value and ability to generate foreign exchange for the country. Analysis of the factors affecting Indonesia's tuna exports to Japan is very important based on Japan's position as the main export market for Indonesian tuna in order to help formulate effective policies in increasing the competitiveness and volume of Indonesian tuna exports. Therefore, the purpose of this research is to analyze the effect of tuna fish production in Indonesia, the real price of tuna fish exports, and the real rupiah-US dollar exchange rate on the volume of Indonesian tuna fish exports to Japan. The data used is quantitative with secondary data sources from the United Nations Commodity Trade Statistics Database (Un Comtrade), Badan Pusat Statistik (BPS), and Kementerian Kelautan dan Perikanan (KKP) from 2009 to 2023. Time series data for 15 years were analyzed using multiple linear regression models (Ordinary Least Square). The results showed that simultaneously, production variables, real prices, and real exchange rates had a significant influence on the volume of Indonesian tuna exports to Japan. However, partially, only the real exchange rate has a significant effect on export volume but the direction of the effect is negative, while production and real prices have no significant effect on export volume. Policy recommendations include enhancing production efficiency and product quality through fleet modernization and stronger processing capacity, stabilizing the rupiah exchange rate, and promoting the use of hedging instruments among tuna exporters. These measures aim to mitigate exchange rate risks and strengthen Indonesia’s tuna export competitiveness in high-value markets such as Japan.